127 Demonstration of intracoronary microparticle expression and their association with activated platelet monocyte aggregate in human ST elevation myocardial infarction. (16th May 2012) - Mavroudis, C A; Eleftheriou, D; Majumder, B; Sapsford, R; North, J; Lowdell, M; Brogan, P; Rakhit, R D
Abstract : Background: Platelets play a central role in the pathophysiology of acute coronary syndrome (ACS). During ACS activated platelets express p-selectin which binds to the p-selectin glycoprotein ligand on the monocyte, forming platelet monocyte aggregates (PMA). PMA expression is a sensitive marker of platelet activation. A microparticle (MP) is a submicron membrane vesicle derived from virtually any cell during various biological processes (cell activation, differentiation or apoptosis). Recent experimental and clinical data point towards a causal effect of MP and mainly platelet derived MP [PMP] in the pathogenesis and disease progression of atherosclerosis and coronary artery disease. Aim: To investigate the relationship between levels of intracoronary MP and PMA in ST elevation ACS. Methods: Patients with ST elevation ACS who underwent primary percutaneous coronary angioplasty were recruited. Blood samples for PMA, MP levels and soluble marker of platelet activation (p-selectin) were collected from the infarct related coronary artery. PMA and MP levels were estimated using fluorescent monoclonal antibodies and flow cytometry. CD61+CD14+CD62P+ events are PMA expressing p-Selectin [activated PMA] and CD61+CD14+CD142+ events are PMA expressing tissue factor [TF+ PMA]. Total MPs were identified as AnV+ MP and PMP as AnV+CD42+/or AnV+CD42+CD62+ MP. Endothelial derived MPs (EMP) were identified as AnV+CD105+CD42− events and/or AnV+CD62E+CD42− events. ELISA was used for p-selectin measurement. Results: The mean total AnV+ MP was 3 661 000/ml of plasma. PMP was statistically higher than EMP p=0.01 (mean PMP (SD) 879 986/ml (1 166 000), mean EMP (SD) 89 099/ml (38 867). There was a strongly positive correlation between total Ann V+ MP with intracoronary p-Selectin and activated PMA [r 2 =0.5; p=0.03, r 2 =0.9; p=0.0008 respectively]. PMP correlated positively with intracoronary p-selectin and activated PMA [r 2 =0.7; p=0.01 and r 2 =0.6; p=0.02 respectively] but they also correlated with TF+ PMA [r 2 =0.7; p=0.01]. CD62P+ PMP was strongly positively related with intracoronary p-Selectin [r 2 =0.9; p=0.0001]. CD105+ EMP also correlated positively with intracoronary p-selectin, activated PMA and TF+ PMA [r 2 =0.7; p=0.007, r 2 =0.6; p=0.01 and r 2 =0.5; p=0.04 for intracoronary p-selectin, activated PMA and TF+ PMA respectively]. CD 62E+ EMP positively correlated with intracoronary p-selectin, activated PMA and TF+ PMA [r 2 =0.6; p=0.02, r 2 =0.6; p=0.01 and r 2 =0.5; p=0.03 respectively]. Conclusions: Markers of platelet activation at the site of the culprit lesion during ST elevation ACS correlated strongly not only with total MPs and PMPs but also with endothelial derived MPs. The interaction between activated platelets and monocytes with endothelial cells and the subsequent formation of PMP and EMP during ACS highlights the importance of the downstream effect of activated platelets, monocytes and endothelial cells via MP formation and their contribution in the pathophysiology of ACS.